Nishiaziya no jinruigakuteki kenkyū I, Dēramanisutan kohunbo jinkotsu I - Egami, Namio (1963)
Anthropological Studies of West Asia I, Human Remains from the Tombs in Dailamanistan, Northern Iran. Report V of the Tokyo University Iraq-Iran Expedition.